Green campaign, governance system, and sustainability development goal performance in Indonesian MSMEs - Almilia, Luciana Spica; Mursita, Lufi Yuwana; Mustafida, Nurul; Rachmadia, Rizki; Rohmayati, Nita Selvia (International Journal of Management and Sustainability, 2025)
This study aims to examine the impact of MSMEs’ green campaigns and governance systems on their achievement of the Sustainable Development Goals (SDGs). Motivated by the significant economic contribution of macro, small, and medium enterprises (MSMEs), encouragement for digitalization, and the need to participate in the Sustainable Development Goals (SDGs) agenda. The governance system in this research utilizes operational, technological, financial, and administrative systems. Operational and technological systems in MSMEs include how MSMEs carry out preventive inspections, the level of technology used, the implementation of internet-based applications, the implementation of innovations in quality management systems, and the quality assurance implemented by the company. Using quota sampling in the East Java Province of Indonesia, this study collected data from 414 MSME manager respondents. The research predicts and finds support that green campaigns and parts of governance systems (business, management, operational, and technological systems) positively affect SDG performance. The results show that preventive inspection, technology level, implementation of internet-based applications, and innovation in the quality management system are important factors in the performance of SDG MSMEs in Indonesia. However, no evidence exists that financial and administrative systems affect SDG performance. These findings present several implications for both empirical and practical aspects regarding MSMEs’ participation in achieving SDGs. The practical impact of this research is that MSMEs should prioritize the integration of environmental initiatives into their core business strategies to improve sustainability performance. MSME managers should be willing to invest in these areas to improve operational efficiency and sustainable outcomes.